PENGEMBANGAN MEDIA PEMBELAJARAN APLIKASI PEMBELAJARAN REFRIGERATOR BERBASIS ANDROID PADA MATA KULIAH PERANCANGAN INSTALASI MESIN PENDINGIN DI PROGRAM STUDI PENDIDIKAN TEKNIK ELEKTRO: PENGEMBANGAN MEDIA PEMBELAJARAN APLIKASI PEMBELAJARAN REFRIGERATOR BERBASIS ANDROID PADA MATA KULIAH PERANCANGAN INSTALASI MESIN PENDINGIN DI PROGRAM STUDI PENDIDIKAN TEKNIK ELEKTRO - udiyani komala; I Gede Ratnaya; Wayan Mahardika Prasetya Wiratama (Universitas Pendidikan Ganesha, 2022)
This study aims to create a Hyperlink-Based Digital Learning Module (Lighting Photo) in the Lighting Equipment Course at the Undiksha Electrical Engineering Education Study Program, to find out the feasibility of a 3-light lighting digital learning module in the lighting equipment course, and to find out the responses from students or students. students to this digital learning module. This research, including the type of research R&D (Reasearch and Development). This study uses a descriptive statistical analysis of percentages for the feasibility of small group test and large group test. This study uses a questionnaire as an instrument of data collection by content experts (materials), media experts, and students or students. The results obtained: the digital learning module based on hyoerkibk (lighting photos) and the results of the media expert test got a percentage of 91.6% with very decent qualifications, from the content expert validation test got a percentage of 92.5% with very decent qualifications and trials a small group of 5 respondents who got very decent qualifications. The range of scores for 20 respondents in the large group test is all listed in the very good classification. Hyperlink-Based Learning Module (Lighting Photo) in the Lighting Equipment Course in the Electrical Engineering Education Study Program, Ganesha University, is suitable for use in the learning process.